Perancangan Sistem Penilaian Karyawan Terbaik Menggunakan Metode AHP Dan SAW Pada Inspektorat Situbondo - Jalaludin, Ahmad; Homaidi, Ahmad (Fakultas Teknik Universitas Bhayangkara Surabaya, 2025)
Situbondo Inspectorate. Internship Report, Information Technology Study Program, Ibrahimy University. Supervisor: Ahmad Homaidi, M.Kom.The employee evaluation aims to provide recognition to the best employees in the form of consideration for promotion through a ranking process of employee performance. However, there is still no decision support application or system for the evaluation of the best employees. To address this problem, the author applied the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods with predetermined criteria, namely responsibility, communication skills, initiative, attendance, working age, and attitude. The AHP method is used to determine the weight of each criterion, while the SAW method is applied to determine the best employees by generating alternative rankings. This research is expected to produce criterion weights and generate alternative rankings for selecting the best employees. The system provides useful information in determining the best employees and facilitates the evaluation process. The reports generated by this system include decision result letters, decision result reports, employee evaluation reports, and employee ranking reports. Based on the User Acceptance Test, it can be concluded that users strongly agree with this decision support application and the implementation of the methods. This is evidenced by the 87.5% “strongly agree” result from the User Acceptance Test questionnaire. Keywords: Decision Support System, Best Employee, AHP, SAW.